Characteristics and Outcomes of Pregnant Women Admitted to Hospital With Confirmed SARS-CoV-2 Infection in the UK: National Population-based Cohort Study. Issue 1 (24th March 2021) - Knight, M.; Bunch, K.; Vousden, N.; Morris, E.; Simpson, N.; Gale, C.; O'Brien, P.; Quigley, M.; Brocklehurst, P.; Kurinczuk, J.J.
Abstract : ( BMJ . 2020;369:m2107) Although cases of coronavirus disease 2019 (COVID-19) continue to rise, information on the transmission, effect, and prevalence of the disease in pregnant women and their newborns is still emerging. This study aimed to describe the characteristics and outcomes of a national cohort of pregnant women in the UK hospitalized with COVID-19, the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).